An Empirical Study of Profitability And Liquidity in Selected Auto Two and Three Wheelers Companies in India - Ajmera Tushar Rameshbhai (Journal La Bisecoman, 2022)
The main purpose of any business organisation is profit maximisation and meets current liabilities within a year. Profit is a soul of any business organization and liquidity effectively helps to generate profit for the business. Profitability and liquidity are most important aspect for the organisation to fulfil their desired goal. In this empirical study attempt is made for identification of profitability and liquidity in auto two and three wheelers companies, which are listed on stock exchange. The time span of 2011-12 to 2018-19 should be considered for the study and randomly three companies are selected for analysis and findings purposes. The major finding of the study Baja auto indicated comparative good profitability but hero motorcorps reveals comparative higher ratio out of selected companies. Hero Motorcorps and Bajaj auto have good comparative liquidity position then TVS Motors. In concern with statistical test Anova except Debtors turnover ratio all selected ratio are rejected mean selected companies have no significant difference in debtors turnover ratio during study period.